Treatment of the Lower Extremity Contracture/Deformities. Issue 5 (July 2017) - van Bosse, Harold J.P.; Pontén, Eva; Wada, Akifusa; Agranovich, Olga E.; Kowalczyk, Bartłomiej; Lebel, Ehud; Şenaran, Hakan; Derevianko, Denis V.; Vavilov, Maxim A.; Petrova, Ekaterina V.; Barsukov, Dmitry B.; Batkin, Sergey F.; et al.
Abstract : Lower extremity deformities of patients with arthrogryposis multiplex congenita present a wide spectrum of severity and deformity combinations. Treatment goals range from merely ensuring comfortable seating and shoe wear, to fully independent and active ambulation, but the overarching intention is to help realize the patient's greatest potential for independence and function. Treatment of hip and knee contractures and dislocations has become more interventional, whereas treatment of foot deformities has paradoxically become much less surgical. This article synopsizes the treatment strategies presented in September 2014 in Saint Petersburg, Russia at the second international symposium on arthrogryposis.